Webcam consultations for diabetes: findings from four years of experience in Newham. (March 2017) - Morris, Joanne; Campbell‐Richards, Desiree; Wherton, Joseph; Sudra, Rita; Vijayaraghavan, Shanti; Greenhalgh, Trisha; Collard, Anna; Byrne, Emma; O'Shea, Teresa
Abstract: Newham diabetes service supports an ethnically diverse population in a deprived urban area and exemplifies challenges faced throughout the NHS with rising demand, high outpatient 'did not attend' (DNA) rates (33–50% depending on age) and poor health outcomes. With funding from the Health Foundation, we aimed to provide more accessible and cost‐effective care by replacing selected follow‐up outpatient appointments with webcam consultations. This paper reports a mixed methods evaluation comprising attendance and biomarker data, and patient and staff interviews. Consultations were offered to clinically suitable adults aged over 18 and supported using everyday technology available in most people's homes (computer or smartphone, Wi‐Fi connection). From 2011–2014, 480 online appointments were scheduled by one consultant and one diabetes specialist nurse. Overall, the DNA rate was 13% (compared to 28% for all outpatient appointments for the same patients). There were an additional 152 'patient‐initiated' webcam appointments (in which patients made contact for a Skype consultation in between their scheduled appointments). Quantitative data were inconclusive, although an improvement in HbA1c levels (though not statistically significant) was evident for those using the webcam service. A&E attendance data showed greater uncertainty, partly due to the relatively small number of A&E events. Qualitative data indicated that patients found the service convenient, empowering and dependent on a pre‐existing relationship with their clinician, and delivering as good a quality of care as face to face. Patients and staff felt that webcam appointments were not appropriate for all encounters, but could be interspersed with traditional clinic visits. No critical incidents occurred. Modest efficiency savings were identified, through a decrease in DNAs and increased productivity – with clear savings for patients. Further work is ongoing to understand system‐wide changes required to embed this intervention longer term. Copyright © 2017 John Wiley & Sons.